Raw milk quality: the processor's point of view - Karen A. Schmidt (Kansas Agricultural Experiment Station Research Reports, 2000)
Raw milk quality is important to the processor for many reasons, this quality can be assessed by several different tests. Quality tests are used to ensure that the raw milk meets legal USDA standards as well as some of the individual requirements of the processor. Although some quality tests can be done in a matter of minutes, others require up to several days to complete. Because milk quality deteriorates relatively quickly, it is important to concentrate on those tests that provide the greatest amount of information in the shortest time. This information then is extrapolated to assess the "actual raw milk quality". After all, the quality of milk does not improve with time; thus, if the starting materials are substandard, the final products will be less than substandard. Generally, raw milk quality is assessed by type and number of microbes, milk composition, presence of contaminants, and current (and perhaps previous) temperature.; Dairy Day, 2000, Kansas State University, Manhattan, KS, 2000;
Keywords: Dairy Day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-166-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 861; Dairy; Raw milk; Quality; Incoming tests